2-Dichloromethyl-N-ethyl-5-(1-phenylsilolan-1-yl)cyclopent-3-enecarboxamide - Han Xiao; Wan-Qiu Yang; Liang Shen (Acta Crystallographica Section E, 2013)
In the title compound, C19H25Cl2NOSi, the NH group and the carbonyl O atom of the amide fragment are involved in an intermolecular N—H...O hydrogen bond forming chains of molecules. The plane of the benzene ring forms a dihedral angle of 50.5 (2)° with respect to the silolane ring and an angle of 49.74 (2)° with the cyclopentyl moiety.